After Brown : The Rise and Retreat of School Desegregation - Clotfelter, Charles T. (Book collections on Project MUSE., 2004)
The United States Supreme Court's 1954 landmark decision, Brown v. Board of Education, set into motion a process of desegregation that would eventually transform American public schools. This book provides a comprehensive and up-to-date assessment of how Brown's most visible effect--contact between students of different racial groups--has changed over the fifty years since the decision. Using both published and unpublished data on school enrollments from across the country, Charles Clotfelter uses measures of interracial contact, racial isolation, and segregation to chronicle the changes. He goes beyond previous studies by drawing on heretofore unanalyzed enrollment data covering the first decade after Brown, calculating segregation for metropolitan areas rather than just school districts, accounting for private schools, presenting recent information on segregation within schools, and measuring segregation in college enrollment. Two main conclusions emerge. First, interracial contact in American schools and colleges increased markedly over the period, with the most dramatic changes occurring in the previously segregated South. Second, despite this change, four main factors prevented even larger increases: white reluctance to accept racially mixed schools, the multiplicity of options for avoiding such schools, the willingness of local officials to accommodate the wishes of reluctant whites, and the eventual loss of will on the part of those who had been the strongest protagonists in the push for desegregation. Thus decreases in segregation within districts were partially offset by growing disparities between districts and by selected increases in private school enrollment. ... Publisher description.